PEMANFAATAN PERMAINAN TRADISIONAL DALAM PEMBELAJARAN ANAK USIA DINI DI TAMAN KANAK-KANAK SE-KECAMATAN PONTIANAK TIMUR - Addina Nuristiqomah; Aloysius Mering; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study was intended to determine the use of traditional games in learning in kindergarten in East Pontianak Regency. Research Methods The method used is a quantitative method with the type of survey research. The community in this study, kindergarten teachers in East Pontianak Regency with a total sampling technique. The tool used to collect data is a questionnaire. The results showed that the use of traditional games in learning in kindergartens throughout East Pontianak Regency as a whole was included in the poor category with a percentage of 66.7%, which means that teachers sometimes use traditional games as a learning method. The results showed (1) the implementation of traditional games in children's learning from an early age by teachers in kindergartens in East Pontianak was included in the good category with appercentage of 70.4% which means that teachers often apply traditional games in learning for young children early. (2) Types of games traditional method applied by teachers as a learning method in Kindergarten Children in East Pontianak Sub-district are in the poor category with the percentage of 44.4% means that there are 14 traditional games that are applied (3) UK understanding of kindergarten teachers in East Pontianak Regency on the benefits of traditional game players in improving aspects of child development including with a percentage of 74.1% in the category of teachers have not been able to understand the benefits of traditional games.